The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1166/jnn.2016.10889
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Temperature-Dependent Upconversion Luminescence of α-NaYF4:Yb3+/Er3+ Nanocrystals Synthesized by a Microwave-Assisted Hydrothermal Method

Abstract: Yb³⁺/Er³⁺co-doped cubic-(α-) phase NaYF₄ nanocrystals were prepared through a microwave- assisted hydrothermal method. Temperature-dependent upconversion luminescence (UCL) and sensing properties were systematically studied. It is interesting that anomalous temperature- dependent UCL behavior is observed. With increasing temperature (303-573 K), the UCL intensity of Er³⁺ does not quench monotonously but reaches a minimum around 483 K and then increases. However, it was found that the UCL spectra change in a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In 2016, Tong et al reported an interesting temperaturedependent UCL variation of Yb 3+ /Er 3+ co-doped α-NaYF4 NPs with a size of around 75 nm. 45 As temperature increased, the UCL intensity of Er 3+ gradually decreased to a minimum at 483 K and then it increased as temperature further increased to 573 K. Upon cooling, the UCL intensity was recovered (as usual), while a similar but rather weaker "decrease-increase" emission intensity variation reappeared in the subsequent heating phase. The authors suggested that this anomaly was induced by the "adsorption-desorption" process of a small amount of H2O molecules and other organic solvent residuals on the particle surface at different temperatures.…”
Section: Deeper Understandings Of the Thermal Enhancement Mechanismmentioning
confidence: 69%
“…In 2016, Tong et al reported an interesting temperaturedependent UCL variation of Yb 3+ /Er 3+ co-doped α-NaYF4 NPs with a size of around 75 nm. 45 As temperature increased, the UCL intensity of Er 3+ gradually decreased to a minimum at 483 K and then it increased as temperature further increased to 573 K. Upon cooling, the UCL intensity was recovered (as usual), while a similar but rather weaker "decrease-increase" emission intensity variation reappeared in the subsequent heating phase. The authors suggested that this anomaly was induced by the "adsorption-desorption" process of a small amount of H2O molecules and other organic solvent residuals on the particle surface at different temperatures.…”
Section: Deeper Understandings Of the Thermal Enhancement Mechanismmentioning
confidence: 69%
“…Moreover, the position of the band varies with different kinds of alkyl layers. Clearly, these discriminations in PL behavior were caused by the capped alkyl ligands, rather than the crystal lattice vibration of the UCNPs as proposed by others previously. Such phenomenon may be related to the temperature-induced ligand layer reorientation, such as decreased tilt angles and increased layer thickness of alkyl chains. , Except for temperature, the ligand conformation could be changed by other external stimulations such as solvents. ,, Although the ligand conformation can be largely maintained in the “good” solvent such as cyclohexane and CCl 4 , the case may be quite different in other solvents.…”
Section: Resultsmentioning
confidence: 76%
“…Besides the surface curvature, it is worthy of emphasizing that the PL behaviors of inorganic NPs are also vulnerable to the ligand conformation when varying the external environments. For example, the influence of temperature on PL behaviors of UCNPs has been extensively studied previously for the possible application in temperature sensing, but the change of ligand conformation with temperature on the surface of UCNPs is neglected for long. A preliminary experiment here shows that different from the gradual PL decreases with increasing temperature from 45 to 65 °C for the ligand-free samples, a broad band of the PL intensity curve was observed for the NPs capped with alkyl ligands (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the UC intensity of SLA:Er is too low to be used practically in comparision to the SLA:Er/Yb samples. From literature it is also evident that the sensitivity of SLA:Er and SLA:Er/Yb phosphors are also in accordance to the low phonon hosts such as fluorides, rare earth oxides etc that are highly used in bio-imaging due to their high UC efficiencies in spite of their toxic nature 1,5054 .…”
Section: Resultsmentioning
confidence: 81%